The Issues Related to Children with Leukemia in Indonesia: An Integrative Review - Siti Arifah; Autchareeya Patoomwan (Jurnal Berita Ilmu Keperawatan, 2023)
This integrative review, based on twenty-four studies from data resources, including Scopus, CINAHL, MEDLINE, PsycINFO, and Indonesia science and technology index (SINTA), was published from 2009 to 2019. The eligible studies were conducted in Indonesia, published in the English or Indonesian language, and reported the incident, survival rate, and physical or psychological effects of disease or chemotherapy. There were 23 quantitative studies and two qualitative studies. The theoretical or conceptual framework was not identified to guide and develop the studies. Most studies used retrospective and cross-sectional studies; the target population was acute lymphoblastic leukemia (ALL) and used small sample sizes for a cross-sectional study. The variables that were explored in the quantitative studies consisted of the incidence of leukemia, survival rate, abandonment of treatment, effects of disease or chemotherapy, quality of life (QOL), and others. The qualitative findings focused on the experience of being diagnosed with leukemia and its meaning in the adolescent context. The evidence from the studies showed that the incidence rate of all types of leukemia increases each year. The survival rate was lower than in other countries, with differences in numbers among hospitals. The effects of the disease and chemotherapy dominated the problem of children the low level of QOL. More research is necessary to explore the factors related to treatments' outcomes, particularly the aspects related to survival rate and QOL are using comprehensive data analysis, an appropriate theoretical framework to guide the study, more sample size, and involving multiple hospital settings.